2015
DOI: 10.1182/blood-2014-06-581082
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of EZH2 and EZH1 enzymatic activity by a small molecule suppresses MLL-rearranged leukemia

Abstract: Key Points We characterize active vs inactive analog compounds suitable for inhibition of both PRC2-EZH2 and PRC2-EZH1 ex vivo and in vivo. This study is the first to show oral delivery of an EZH2 and EZH1 dual inhibitor as promising therapeutics for MLL-rearranged leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(205 citation statements)
references
References 57 publications
11
193
0
1
Order By: Relevance
“…Therefore, it is not possible to conclude that the diminution of memory by compound is a result of changing H3K27me3 levels as reduced transcription could also be at play. We then asked if globally reducing the levels of H3K27me3 with the Ezh2 inhibitor UNC1999 (34) in the absence of a C/EBP␣ pulse could impart the same transcriptional memory phenomenon. Following the experimental design depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not possible to conclude that the diminution of memory by compound is a result of changing H3K27me3 levels as reduced transcription could also be at play. We then asked if globally reducing the levels of H3K27me3 with the Ezh2 inhibitor UNC1999 (34) in the absence of a C/EBP␣ pulse could impart the same transcriptional memory phenomenon. Following the experimental design depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The level of H3K27me3 at enhancers is generally low, making it difficult to draw conclusions based exclusively on ChIP studies. Therefore, to substantiate the importance of H3K27 demethylation on memory establishment and retention, we used small-molecule inhibitors that impair the enzymatic activity of the H3K27me3 demethylases and methylases, namely, Jmjd3/Utx (inhibited by glycogen synthase kinase [GSK]-J1/J4) (33) and Ezh1/2 (inhibited by UNC1999) (34). If H3K27 demethylation and retention contribute to memory, then blocking demethylation during the pulse should reduce the memory effect.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, EZH1 mRNA (Figure 4(B)) and protein (Figure 4(C)) levels were suppressed by miR-17-5p mimic but increased by miR-17-5p inhibitor. As previous studies have shown that Cdkn2a is an important target of EZH1 and EZH1 represses Cdkn2a expression [27,28], we also measured the Cdkn2a levels. The results showed that miR-17-5p mimic increased Cdkn2a level while miR-17-5p inhibitor reduced Cdkn2a level (Figure 4(C)).…”
Section: Ezh1 Is a Target Of Mir-17-5pmentioning
confidence: 99%
“…Recently, it was suggested that EZH2 inhibitors are also effective in the treatment of AML (41). Thus, the potential for KDM1A inhibitors to work in combination with EZH2 inhibitors was investigated.…”
Section: Kdm1a Inhibitors Combine With Other Agents For the Treatmentmentioning
confidence: 99%